Pengaruh Pembelajaran PJOK Materi Lari 100 m Berbasis Outbound Game untuk Meningkatkan Hasil Belajar Siswa SD Negeri Gamer 02 Kcamatan Pekalongan Timur - S. Moch Tri Surya Alam; Maftukin Hudah; Galih Dwi Pradipta (Journal of Creative Student Research, 2025)
This research started from the problem of low student learning outcomes in learning PJOK 100 m running material at SD Negeri Gamer 02, East Pekalongan District. Initial observation results show that there are still 17 students who obtained learning outcomes below the KKM (75.00). By looking at this reality, it is necessary to make improvements through the implementation of an appropriate, effective and efficient PJOK learning model. Researchers attempt to overcome this problem by implementing outbound game-based PJOK learning and finding out its effect on student learning outcomes.The experimental method was used in research with a one group pretest-posttest design. The research population was all students at SD Negeri Gamer 02, East Pekalongan District. The samples taken in this research were all 30 class V students. The research variables consist of the independent variable, namely PJOK learning, 100 m running material based on outbound games and the dependent variable, namely student learning outcomes. The research results were obtained through statistical tests of variables and obtained a calculated t value of 27.114 > t table 2.045 (df 29) with a significance p value of 0.000 < 0.05. Judging from the average value of student learning outcomes in PJOK learning 100 m running material, the pre-test data obtained had a mean of 71.59, then during the post-test the mean reached 76.21. The magnitude of the increase in student learning outcomes can be seen from the difference in average scores, namely 4.62. From the mean difference, the percentage increase can be seen by dividing the mean difference by the post-test mean multiplied by 100%, amounting to 6.06%, so this result shows that there is a significant influence. Based on the results of the research and discussion, it can be concluded that learning PJOK material on 100 m running based on outbound games has a positive and significant effect on the learning outcomes of class V students at SD Negeri Gamer 02, East Pekalongan District. The PJOK learning method for the 100 m running material based on outbound games has a significant influence on student learning outcomes. Choosing the right method will be able to have a maximum contribution to improving student learning outcomes. Packaging training programs that are tailored to the abilities and level of difficulty of the basic techniques being taught can provide significant changes in improving student learning outcomes.